"Central Asia: democracy, instability and strategic game in Kyrgyzstan" - "Stobdan, P." (New Delhi, 2014)
Central Asia remains both stable and unpredictable after 20 years of its reemergence. The states here continue to undergo a complex nation-building process, which is far from complete, but they firmly remain insulted by Russia China. Only Kyrgyzstan has so far uniquely follow in liberal polity, but this young country had a cope with two revolutions before achieving a parliamentary democracy in 2010.
Keywords: Kyrgyzstan